The State of Application of Electronic Education System in Azerbaijan - Arzu Huseynova, Ophelya Mazanova, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article deals with the application of electronic management systems in the higher education system, the increase of electronic resources, the ways to ensure employment and convenience for teachers and students, the implementation of social reading programs apart from traditional lectures in the training classes, provision of information security, and elimination of electronic backwardness. The article also discusses the use analysis of electronic education system in Azerbaijani higher education institutions and evaluation methods of its economic effectiveness. Created a questionnaire to analyze e-learning, traditional training, and mixed learning. The questionnaire covers 20 electronic resources. The level of use of electronic means in the training process was analyzed based on the survey questionnaire. Survey questionnaire was conducted between teachers and students of higher education institutions. Cluster, regression, SWOT, and PEST analysis methods were used in the process of query processing. As a result, it was recommended to develop a strategy for the electronic education system and to develop a human resources training system for innovative Technologies.